Impact of Prior Antibiotic Use in Primary Care on Escherichia coli Resistance to Third Generation Cephalosporins: A Case-Control Study - Chiara Fulgenzio; Marco Massari; Giuseppe Traversa; Roberto Da Cas; Gianluigi Ferrante; Richard Aschbacher; Verena Moser; Elisabetta Pagani; Anna Rita Vestri; Orietta Massidda; Peter Konstantin Kurotschka (MDPI AG, 2021)
Research is lacking on the reversibility of antimicrobial resistance (AMR). Thus, we aimed to determine the influence of previous antibiotic use on the development and decay over time of third generation cephalosporin (3GC)-resistance of E. coli. Using the database of hospital laboratories of the Autonomous Province of Bolzano/Bozen (Italy), anonymously linked to the database of outpatient pharmaceutical prescriptions and the hospital discharge record database, this matched case-control study was conducted including as cases all those who have had a positive culture from any site for 3GC resistant E. coli (3GCREC) during a 2016 hospital stay. Data were analyzed by conditional logistic regression. 244 cases were matched to 1553 controls by the date of the first isolate. Male sex (OR 1.49, 95% CI 1.10-2.01), older age (OR 1.11, 95% CI 1.02-1.21), the number of different antibiotics taken in the previous five years (OR 1.20, 95% CI 1.08-1.33), at least one antibiotic prescription in the previous year (OR 1.92, 95% CI 1.36-2.71), and the diagnosis of diabetes (OR 1.57, 95% CI 1.08-2.30) were independent risk factors for 3GCREC colonization/infection. Patients who last received an antibiotic prescription two years or three to five years before hospitalization showed non-significant differences with controls (OR 0.97, 95% CI 0.68-1.38 and OR 0.85, 95% CI 0.59-1.24), compared to an OR of 1.92 (95% CI 1.36-2.71) in those receiving antibiotics in the year preceding hospitalization. The effect of previous antibiotic use on 3GC-resistance of E. coli is highest after greater cumulative exposure to any antibiotic as well as to 3GCs and in the first 12 months after antibiotics are taken and then decreases progressively.